2004
DOI: 10.1017/s0021932004006649
|View full text |Cite
|
Sign up to set email alerts
|

Advocating Multi-Disciplinarity in Studying Complex Emergencies: The Limitations of a Psychological Approach to Understanding How Young People Cope With Prolonged Conflict in Gaza

Abstract: The paper looks at the limitations and strengths of using the A-cope questionnaire for measuring strategies for coping with prolonged conflict by Palestinian young people in Gaza. The scale was administered to young people between the ages of 8 and 17. The results show some gender differences in coping strategies. However, some items on the subscales are not relevant for Muslim societies or societies in situations of prolonged conflict. The authors suggest that combining an anthropological contextual perspecti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
1

Year Published

2010
2010
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 25 publications
(2 citation statements)
references
References 26 publications
0
1
1
Order By: Relevance
“…Our results were consistent with the previous studies in the Gaza Strip. 30,[32][33][34]43 Our results were inconsistent with the results that found children used instrumental social support (81.2%), instrumental emotional support (75.9%), religious coping (59.8%), and humor (50.8%). 44 Also, others found that a majority of the children's coping responses in the study of stressors and coping behaviors of school-aged homeless children staying in shelters were in the social support (86%), cognitive avoidance (38%), and behavioral distraction categories (31%).…”
Section: Discussioncontrasting
confidence: 82%
“…Our results were consistent with the previous studies in the Gaza Strip. 30,[32][33][34]43 Our results were inconsistent with the results that found children used instrumental social support (81.2%), instrumental emotional support (75.9%), religious coping (59.8%), and humor (50.8%). 44 Also, others found that a majority of the children's coping responses in the study of stressors and coping behaviors of school-aged homeless children staying in shelters were in the social support (86%), cognitive avoidance (38%), and behavioral distraction categories (31%).…”
Section: Discussioncontrasting
confidence: 82%
“…The interaction between people and their environments, as well as the experiences of individuals, indicate the social construction of resilience as a holistic phenomenon. The studies done in colonial contexts with a history of systematic marginalization called into question the notion of resilience as a quantifiable construct and urged that social resilience be conceptualized and researched as a dynamic and complex phenomenon (Bogardi & Fekete, 2018;Atallah, 2016;Hundt et al, 2004;Dagdeviren & Donoghue, 2019;Qamar, 2023).…”
Section: выводыmentioning
confidence: 99%